Deconstruyendo el yo disciplinar: el vínculo entre ciencia política y teoría política en América Latina. (2020)
This article reflects on the relationship between political science and political theory in Latin America. On the one hand, we argue that the way political theory is treated by mainstream political science reveals some of the most problematic ‘personality traits’ of the latter. On the other hand, we suggest that – if allowed – political theory can contribute to maintain and cultivate pluralism in the discipline, thus strengthening its democratic imagination. Hence, we contend that there is much at stake in the relationship between political science and political theory in the region. Although the article draws on research agendas focused on critical theory and on the study of power and knowledge dynamics within political science, we also offer an experiential and subjective perspective that we deem necessary to underscore. We aim to foster debate and to generate the conditions for political theory to be heard.